Engineering high-performance Pd core–MgO porous shell nanocatalysts via heterogeneous gas-phase synthesis. Issue 32 (23rd July 2015) - Singh, Vidyadhar; Cassidy, Cathal; Abild-Pedersen, Frank; Kim, Jeong-Hwan; Aranishi, Kengo; Kumar, Sushant; Lal, Chhagan; Gspan, Christian; Grogger, Werner; Sowwan, Mukhles
Abstract : The porous MgO shell inhibited the sintering/coalescence of the Pd nanoparticles, while preserving their catalytic activity. Abstract : We report on the design and synthesis of high performance catalytic nanoparticles with a robust geometry via magnetron-sputter inert-gas condensation. Sputtering of Pd and Mg from two independent neighbouring targets enabled heterogeneous condensation and growth of nanoparticles with controlled Pd core–MgO porous shell structure. The thickness of the shell and the number of cores within each nanoparticle could be tailored by adjusting the respective sputtering powers. The nanoparticles were directly deposited on glassy carbon electrodes, and their catalytic activity towards methanol oxidation was examined by cyclic voltammetry. The measurements indicated that the catalytic activity was superior to conventional bare Pd nanoparticles. As confirmed by electron microscopy imaging and supported by density-functional theory (DFT) calculations, we attribute the improved catalytic performance primarily to inhibition of Pd core sintering during the catalytic process by the metal-oxide shell.